2014
DOI: 10.1111/and.12326
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between human spermatozoa-hyaluronan-binding assay, conventional semen parameters and fertilisation rates in intracytoplasmic spermatozoa injection

Abstract: Selecting the best spermatozoa for intracytoplasmic spermatozoa injection (ICSI) has recently been a topic of great interest among embryologists. The study aimed to evaluate the relationship between the spermatozoa-hyaluronan-binding assay (HBA), routine semen analysis results and fertilisation rates as recorded during conventional ICSI therapy. Ninety-one patients undergoing conventional ICSI treatment in the Medfem Fertility Clinic in Johannesburg (South Africa) were included in the study. A total of 797 ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In human, HBA represents a convenient and reproducible laboratory test for identifying candidates and assigning them for IVF or ICSI (Cayli et al., ; Huszar et al., ). HBA values in pregnant women were numerically higher than those in the non‐pregnant group, although not statistically significant (Esterhuizen et al., ). HBA does not predict the IUI outcome in couples with unexplained infertility or mild male factor infertility, as well as it cannot replace sperm penetration assays, but it can be used together with other semen parameters to verify sperm quality (Lazarevic et al., ; Yildirim, Duvan, Pekel, Ayrim, & Kafali, ).…”
Section: Review Of Sperm Functional Testsmentioning
confidence: 99%
“…In human, HBA represents a convenient and reproducible laboratory test for identifying candidates and assigning them for IVF or ICSI (Cayli et al., ; Huszar et al., ). HBA values in pregnant women were numerically higher than those in the non‐pregnant group, although not statistically significant (Esterhuizen et al., ). HBA does not predict the IUI outcome in couples with unexplained infertility or mild male factor infertility, as well as it cannot replace sperm penetration assays, but it can be used together with other semen parameters to verify sperm quality (Lazarevic et al., ; Yildirim, Duvan, Pekel, Ayrim, & Kafali, ).…”
Section: Review Of Sperm Functional Testsmentioning
confidence: 99%
“…All studies were considered of undetermined quality given that exclusion criteria were either illdefined or included pathologies which may impact later outcomes, e.g., endometriosis. [26,31,[44][45][46][47][48].…”
Section: Can Assessment Of Sperm Function By Ha-binding Predict Clini...mentioning
confidence: 99%
“…Six of the included studies reported fertilisation rates [31,[44][45][46][47][48]. Esterhuizen et al calculated the HAB score of raw semen samples in 91 couples undergoing conventional ICSI, reporting a significant positive correlation between HAB score and fertilisation rates (R = 0.60, p = 0.0001) [44].…”
Section: Fertilisation Rate (Fr)mentioning
confidence: 99%
See 2 more Smart Citations